A transcendência do direito do trabalho das fronteiras da relação empregatícia: novas formas de contratação e superação do discurso de precarização e fraudes nas relações trabalhistas - Frederico Nogueira Feres (2024)
This study, supported by the deductive method of approach, as starting from generalization to reach a particularized question, was based on the objective of studying the new forms of service provision that emerged within the scope of Labor Law, based on the professional categories established in light of the articles 2 and 3 of the Consolidation of Labor Laws – CLT (Law No. 5,452, of May 1, 1943): pejotization and statutory direction, in the theoretical context imposed on them by the regulatory legislation of the recent Labor Reform: Law nº 13.429, of March 13, 2017, and Law nº 13.467, of July 13, 2017. Professional categories that received specific regulation and authorization, to sign a service provision contract different from that provided for in the CLT, given the legislator's intention to favor the use of specialized labor without the obligation to register in a portfolio. In the context of such a proposal, the following were investigated: (i) the characteristics responsible for the recent changes in the legal system regulating the employment relationship since the institution of the CLT – Law nº 5.452, on May 1, 1943; (ii) the basic principles of Labor Law, adding to those present in the CLT the innovative Principle of Minimum Intervention in Labor Matters; (iii) specific statutory management contracts without an employment relationship as a way of applying articles 2 and 3 of the CLT; (iv) the development of technology as a contribution to the modernization of Labor Law; (v) the absence of an employment relationship in the pejotização and statutory director employment modalities; (vi) the presence of different levels of hierarchical dependence in the labor market as an element that guarantees the absence of homogeneous and compact treatment in the current employment relationship; and (vii) the risk that the interpreter of Labor Law runs of treating unequal situations equally, that is, of creating inequality through equality. At the end of this study, from the point of view of the proposed main objective, it was concluded that the Labor Reform, brought about by Law nº 13.429/2017 and Law nº 13.467/2017, delimited the quadrant within which the spaces for free negotiation between parts now allow the employer to act legally more securely. Thus, considering that the employer's discretion cannot be unrestricted, a balance was finally achieved between the parties: employer/employee, with the understanding that Labor Law must always take into account that work is an action carried out by human beings. humans .